KAPABILITAS INOVASI ORGANISASI SEBAGAI MEKANISME PENGHUBUNG ANTARA STRATEGIC HUMAN RESOURCE MANAGEMENT DAN KINERJA UMKM - Perwira, Iwan; Hernita, Hernita; Basri, Muhammad; Ayu Kusumaningrum, Retno; Hasfi, Wirawan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This research aims to explore the impact of Strategic Human Resource Management (SHRM) on the performance of Micro, Small, and Medium Enterprises (MSMEs) and to identify the role of organisational innovation capability as a mediator in this relationship. Employing a quantitative method, a survey was conducted involving 125 MSME practitioners in Gowa Regency, South Sulawesi, using purposive sampling techniques. The selection criteria for respondents included businesses that have been operational for a minimum of two years and possess a workforce. The data collected were subsequently analysed using path analysis and the Sobel mediation test. The findings indicate that SHRM has a significant positive effect on innovation capability (β = 0.563; p < 0.05) and on MSME performance (β = 0.271; p < 0.05). Furthermore, innovation capability positively contributes to enhancing MSME performance (β = 0.468; p < 0.05). The Sobel test confirms that innovation capability serves as a significant mediating variable in the relationship between SHRM and MSME performance (z = 3.874; p < 0.05). These findings underscore the importance of implementing strategic human resource management practices to enhance MSME performance through innovation, where the development of competencies and an innovation culture are pivotal strategies for improving competitiveness.